Percutaneous Portal Vein Access and Transhepatic Tract Hemostasis - Saad, Wael E. A.; Madoff, David C. (Seminars in Interventional Radiology, 2012)
Percutaneous portal vein interventions require minimally invasive access to the portal venous system. Common approaches to the portal vein include transjugular hepatic vein to portal vein access and direct transhepatic portal vein access. A major concern of the transhepatic route is the risk of postprocedural bleeding, which is increased when patients are anticoagulated or receiving pharmaceutical thrombolytic therapy. Thus percutaneous portal vein access and subsequent closure are important technical parts of percutaneous portal vein procedures. At present, various techniques have been used for either portal access or subsequent transhepatic tract closure and hemostasis. Regardless of the method used, meticulous technique is required to achieve the overall safety and effectiveness of portal venous procedures. This article reviews the various techniques of percutaneous transhepatic portal vein access and the various closure and hemostatic methods used to reduce the risk of postprocedural bleeding.
Keywords: Liver; percutaneous; coils; glue (N-butyl cyanoacrylate); Gelfoam; portal vein; hemostasis